PENGARUH PEMBERIAN KOMPOS TANDAN KOSONG (KOTAK PLUS) TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SELADA MERAH (Lactuca sativa Var. crispa) SECARA VERTIKULTUR - Angga Aprinaldi. Elfi Indrawanis. A. Haitami (Fakultas Pertanian, Program Studi Agroteknologi, 2019)
This study aims to determine the effect of giving empty bunch compost (KOTAKPLUS) on the growth and production of red lettuce (Lactuca sativa Var. Crispa) verticulture. This study used a non-factorial randomized block design (RBD) with 5 levels of treatment, namely the provision of empty bunch compost (KOTAKPLUS) consisting of: A0 = Top soil, A1 = 3: 1 ratio (Top Soil: (KOTAKPLUS), A2 = Comparison 2: 2 (Top Soil: KOTAKPLUS). A3 = Ratio 1: 3 (Top Soil: KOTAKPLUS), and A4 = Box Plus 100%. The parameters observed consisted of Plant Height (cm), Number of Leaves (cm), Leaf Width (cm ), Plant Weight per Plot (kg), and Consumption Weight per Plot (kg). Based on the results of the study, it can be concluded that the provision of empty bunch compost (KOTAKPLUS) has a significant effect on all growth parameters and production of red lettuce (Lactuca sativa Var. Crispa) ) verticulture, with the best treatment found in the A3 (Top Soil 1: 3 Compost KOTAKPLUS) treatment, with an average plant height of 13.40 cm, number of leaves 9.67, leaf width 8.98 cm, plant weight per plot of 3.17 kg, and consumption weight per plot of 2.28 kg . Maximum Extract 250-300 words in Indonesian and English with 11 points Arial. Abstract must be clear, descriptive and must provide a brief description of the problem being carried out / researched. Abstract includes the reasons for selecting the topic or the importance of the research topic, research methods and a summary of the results. The abstract should end with a comment about the importance of the result or a brief conclusion